The Flying Bike - Mohammed Mohammed AL-Mutlack (Iraqi Journal of Architecture and Planning, 2018)
Â Â The dream of the man to fly like a bird or butterflyis an old one . He Trys hard to achieve it in a way or another and his efforts lead him to discover a lot of amazing discoveries that change the style of his life But the Man does not able to fly until he identified the basics of the flying principles. So he made the primary modeles of planes at the ends of the 19 th century soon after he had innovated the ordinary bicycle . The science of flying developed quickly and reached the present advanced techniques, but the devise of the Man to fly in a conventional way like a bird without burning fuel still occupy his mind . So he found the different types of parachutes and some types of flying suits like squirrel suit and others in order to fly freely for several minutes . The Man perceives that the real enjoyment in flying comes from imitating the birds. Here I start to find a suitable way which can collect all the requirements to apply all the known flying principles that lead to mechanical device avoiding burning fuel and makes the man able to overcome the natural gravity power and finally fly only by means of his muscular efforts ,so that I find the idea of (Flying bike) after doing radical changes in thenechanism of the ordinary bicycle.The action of the Flying bike depends on employment of human biological mechanics to Fly by mechanical vehicle derived by the man and it will Fly him up. That vehicle Can be activated by coordinatedmuscular movements , so it must be on a high degree of manufacturing development , and it must be made of substances that suitable to human body characters and cope with his muscular abilities and that substances have the power ,elasticity and lightness needed to achieve the Known Flying principles which are:-1- The suitable shape for flying which can bechanged as needed.2-Lightweight with required solidity and elasticity.3- The required sail area.4- The mechanism needed to make an alternation in the pressure around the flying body.5- The balloon flight mechanism and the use of helium gas.6-The exceptional useoftheParachute.7- The mechanical lifting of the apical Fan.8- The achievement of the action and counter action rule of the wings.All these principles canbe achieved by the the Flying bike , so this Vehicle canFlyonly by human ability and human will.The Flying Bike as aprojectachieves the following aims :-1-The personal enjoyment specially forthesewho have a desire to fly like a bird.2-The ability to transport freely and quicklybyby- passing the over crowded streets through flying in the sky , particularly in big cities.3-Keep the environment Clean as the Flying bike does not do any pollutions simply because it does not burn any fuel so it has an economic benefits as wall.4-Enhancement of the muscular body fitness so it can be listed with other sport activities so it might be considered as one of Olympicactivities in the nearfuture